Human resources in a healthcare institution as the management efficacy improvement factor - A. V. Kukurika (Исследования и практика в медицине, 2021)
The article analyzes the current HR of the local healthcare organization. There was carried a SWOT-analysis of personnel management has been out, disclosed the main problems of the management system of a medical institution. Development strategies and an algorithm for improving personnel policy are formulated in order to increase the efficiency of management and the quality of medical care to the population.Purpose of the study. Is to analyze the current personnel policy, SWOT-analysis of personnel management, develop a strategies and set of practical recommendations for improving the management system of a public health institution while ensuring high quality medical services to the population.Materials and methods. An analysis of the personnel policy in a phthisiatric institution (Makeevka Municipal TB Dispensary, Donetsk region) was carried out, the heads of the main structural divisions were questioned. The analysis results are structured using the SWOT scale.Results. Based on the results of the sociological survey, the main advantages and disadvantages of personnel policy were identified, a SWOT analysis matrix was drawn up, and strategies for the development of a budgetary healthcare institution were developed. The breakthrough strategy is based on improving the material and technical base, attracting funding and investment, increasing the speed and quality of TB care at the regional level using information technology, while the survival strategy is based on increasing the income of health workers, social protection, improving working conditions and developing personnel motivation systems. The main recommendations include increasing the number of employees, creating a strategy for the formation of qualified personnel, improving the quality of the working environment, creating a favorable psycho-emotional climate, and developing an effective system of incentive payments.Conclusion. The medical industry is in dire need of modernization in order to improve personnel processes, financial, economic and regulatory support. The conducted research and developed recommendations will have a beneficial effect on the achievement of the main strategic goal - improving the health and quality of life of the population of the state.